Parasitic Infections in Stranded Whales and Dolphins in Canary Islands (2018–2022): An Update - Zuleima Suárez-González; Jorge F. González; Manuel Arbelo; Eva Sierra; Ayoze Castro-Alonso; Julia N. Hernández; Vidal Martín; Natalia Fraija-Fernández; Antonio Fernández (Animals)
The Canary Islands are considered a hot spot for marine species biodiversity. Each stranded cetacean has provided important scientific, biological and pathological information. The morphological identification of parasites in these stranded cetaceans is the main aim of the present article. An investigation to identify parasites was carried out in 233 stranded animals (2018–2022), which were submitted for necropsy. Adult and sub-adult/juvenile animals were the most parasitized age categories, and eighteen parasite species were morphologically identified, including nematodes (Crassicauda grampicola, Crassicauda anthonyi, Halocercus delphini, Anisakis simplex, Stenurus globicephalae, Stenurus ovatus), trematodes (Nasitrema delphini, Oschmarinella rochebruni, Brachycladium atlanticum, Pholeter gastrophilus), cestodes (Clistobothrium delphini, Clistobothrium grimaldii), acanthocephalans (Bolbosoma vasculosum, Bolbosoma capitatum), protists (Toxoplasma gondii) and crustaceans (Conchoderma auritum, Xenobalanus globicipitis, Pennella balaenoptera), as well as nine genera: Crassicauda sp., Halocercus sp., Anisakis sp., Stenurus sp., Nasitrema sp., Oschmarinella sp., Dyphyllobothrium sp., Cyamus sp., Conchoderma sp., and Sarcocystis sp. These could not be identified at the species level. Differences in the host specificity of some parasites were observed, varying in prevalence. The accurate morphological identification of the parasites affecting these marine mammals is essential to understanding disease epidemiology, assessing cetacean populations’ health status, and developing effective conservation and management strategies.